Inactivation of the TIM complex components leads to a decrease in the level of DNA import into Arabidopsis mitochondria - T. A. Tarasenko; K. D. Elizova; V. I. Tarasenko; M. V. Koulintchenko; Yu. M. Konstantinov (Вавиловский журнал генетики и селекции)
The phenomenon of DNA import into mitochondria has been shown for all major groups of eukaryotes. In plants and animals, DNA import seems to occur in different ways. It has been known that nucleic acids enter plant organelles through alternative channels, depending on the size of the imported molecules. Mitochondrial import of small DNA (up to 300 bp) partially overlaps with the mechanism of tRNA import, at least at the level of the outer membrane. It is noteworthy that, in plants, tRNA import involves components of the protein import apparatus, whose role in DNA transport has not yet been studied. In this work, we studied the role of individual components of the TIM inner membrane translocase in the process of DNA import into isolated Arabidopsis mitochondria and their possible association with the porin VDAC1. Using knockout mutants for the genes encoding Tim17 or Tim23 protein isoforms, we demonstrated for the first time the involvement of these proteins in the import of DNA fragments of different lengths. In addition, inhibition of transport channels with specific antibodies to VDAC1 led to a decrease in the level of DNA import into wild-type mitochondria, which made it possible to establish the specific involvement of this porin isoform in DNA import. In the tim17-1 knockout mutant, there was an additional decrease in the efficiency of DNA import in the presence of antibodies to VDAC1 compared to the wild type line. The results obtained indicate the involvement of the Tim17-1 and Tim23-2 proteins in the mechanism of DNA import into plant mitochondria. At the same time, Tim23-2 may be part of the channel formed with the participation of VDAC1, while Tim17-1, apparently, is involved in an alternative DNA import pathway independent of VDAC1. The identification of membrane carrier proteins involved in various DNA import pathways will make it possible to use the natural ability of mitochondria to import DNA as a convenient biotechnological tool for transforming the mitochondrial genome.